Integrating enterprise information on demand with XQuery Part I addressing the EII problem. - Carey, Michael
Since the dawn of the database era more than three decades ago, enterprises have been amassing an ever increasing volume of information-both current and historical-about their operations. For the past two of those three decades, the database world has struggled with the problem of somehow integrating information that natively resides in multiple database systems or other information sources.